THE EFFECTIVENESS OF FORCE MAJEUR ON THE CIVIL LAW AND DOCTRIN FRUSTRATION ON THE COMMON LAW SYSTEM IN COMPLETING BUSINESS DISPUTES DURING THE COVID 19 PANDEMIC - Suherman, Yuliana Yuli W, Sonyendah Retnaningsih, Sutrisno, Dyah Sugandini, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The Covid-19 disaster in all countries including Indonesia and Singapore has an impact on the economy in all countries, so that it has a lot of impact on the business world, many companies are unable to carry out their achievements as stated in their business contracts because they are beyond their capabilities which cannot be predicted in when the contract is signed or a force majeure situation. Meanwhile, countries with the Common Law system such as Singapore recognize the existence of doctrine frustration related to the inability of a person or company that cannot carry out their obligations because it is not due to their weakness or incapacity. This type of research is juridical normative, in normative research using secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results show that force majeure is not a specific reason to cancel / terminate a contract (excuse only) while the frustration doctrine can be used to terminate a contract, so that the frustration doctrine will be more effective in resolving business contract disputes during the Covid 19 pandemic because of the consequences if it fails to prove the existence of Frustration of Contrac is considered a refusal to carry out the contract so that the opposing party can ask for compensation for the breach of the contract.